2019
DOI: 10.31487/j.jdoa.2019.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Class III malocclusion camouflage treatment in adults: A Systematic Review

Abstract: Google Scholar, Lilacs, and Cochrane databases, without limitations regarding publication year or language.Studies evaluating nongrowing individuals with Class III malocclusion undergoing orthodontic camouflage treatment with any orthodontic technique, including extraction and non-extraction approaches, were considered. Study selection, data extraction, and risk of bias assessment according to a modified Downs and Black checklist were performed by two independent reviewers. A third evaluator was included if di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…9 However, Class III intermaxillary elastics can promote extrusion of upper molars, proclination of upper incisors, distal tipping of lower molars, and extrusion of lower incisors. 9,10 In some studies, a combination of skeletal anchorage and intermaxillary elastics were used to minimise the unwanted effects of intermaxillary elastics alone. 11,12 This case report demonstrates a camouflage treatment in an adult patient with skeletal Class III malocclusion by the extraction of lower first premolars with the use of intermaxillary elastics and no additional appliances.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, Class III intermaxillary elastics can promote extrusion of upper molars, proclination of upper incisors, distal tipping of lower molars, and extrusion of lower incisors. 9,10 In some studies, a combination of skeletal anchorage and intermaxillary elastics were used to minimise the unwanted effects of intermaxillary elastics alone. 11,12 This case report demonstrates a camouflage treatment in an adult patient with skeletal Class III malocclusion by the extraction of lower first premolars with the use of intermaxillary elastics and no additional appliances.…”
Section: Introductionmentioning
confidence: 99%
“…There were little effects to soft tissue referring to previous studies reported the increases of upper and lower lip thicknesses of 0.7 and 1.2 mm, respectively(73) and a reduction of the H-angle approximately 1.48 degree(74). For class III intermaxillary elastic, the effects were proclination of maxillary incisors, extrusion of maxillary molars, distal tipping of mandibular molars, extrusion of mandibular incisors result in clockwise rotation of the mandibular plane angle and increase in the lower anterior face height(75). There was one case that used temporary anchorage devices (TADs) for camouflaged class III malocclusion producing distal tipping and intrusion of the mandibular molars, bodily movement of the mandibular incisors and reduced mandibular plane angle.…”
mentioning
confidence: 69%